Ø±Ø£Ù Ø£Ø¨Ù ØÙÙÙØ© ÙÙ ÙØ¬ÙØ¯ ÙØ§ÙÙ Ø§ÙØ²ÙØ§Ø¬ - Juliansyahzen, Muhammad Iqbal (Islamic University of Indonesia, 2015)
This paper discusses about the position of guardian in marriage. A marriage certainly has the goal to establish a harmonious family which in the language of religion called by sakinah, mawadah and rahmah. In order to realize the noble purpose of marriage, the majority of scholars consider it important for the guardianship in a marriage as one of the form to preserve the rights of women who are under guardianship. Although most of scholars argued that the guardian as pillars of marriage as adopted in Indonesia by existing any legislation, however there is one who different from the other scholars, he is Imam Abu Hanifah. According to him, the guardian is not included pillars of a marriage. The arguments is used by Abu Hanifa is analogy (qiyas) that mature girl is actually same as the widow. A woman who has grown up in this case as one who would marry is a person of the most understanding of himself. Imam Abu Hanifaâs frameworks more reasonable caused by the social conditions surrounding that metropolitan. Thus, the socio-civic of someone will affect the thinking constructs. Keywords : Guardian, Imam Abu Hanifah, Social-Civic.